Аналіз, оброблення та подання даних у мультимедійних системах - Федорук, М. Ю. (ХНУРЕ, 2025)
The work examines the problem of efficient analysis, processing, and presentation of data in multimedia systems. The proposed approach utilizes machine learning methods for classifying and filtering multimedia data. Experimental results demonstrate the effectiveness of these techniques in optimizing resources and reducing processing delays.
Keywords: подання даних; мультимедійна система